On and off responses of the photopic fullfield ERG in normal subjects and glaucoma patients - Horn, Folkert; Gottschalk, Kristina; Mardin, Christian Y.; Pangeni, Gobinda; Jünemann, Anselm; Kremers, Jan (Documenta Ophthalmologica, 2011)
Recent studies suggest a diagnostic value of the photopic negative response (PhNR) with a long-duration stimulus. The aim of this study was to record the on and off responses of the photopic fullfield electroretinogram (ERG) in normal subjects and glaucoma patients. We focused on different waves of the responses after onset and offset of the long-duration stimulus ERG. Photopic fullfield ERGs were recorded in response to a white bright LED flash on a white 20 cd/m(2) background. Stimulus luminances were 40, 60 and 80 cd/m(2). Responses were averaged using a flash duration of 240 ms and an offset period of 500 ms. We examined 19 healthy subjects, 27 patients with glaucomatous optic disc atrophy and 7 ocular hypertensive patients. The amplitudes and implicit times of the on and off responses of the human ERG depended on flash luminance. Comparing patients with glaucoma and healthy subjects for the 60 cd/m² flash, there was a significant change in the PhNRs (at onset: P < 0.01, at offset: P < 0.001) of the d-wave and of the i-wave at offset (P < 0.01). No significant difference was found for peak times of the fullfield ERG and for a- and b-wave amplitudes. PhNR amplitudes were significantly correlated with mean thickness of retinal nerve fibre layer as measured with OCT. In comparison with the normal photopic long-flash ERG, glaucoma patients showed changes in the PhNR amplitude following stimulus onset and in waves following stimulus offset.
EVALuna2:20998
Keywords: Electroretinogram; Glaucoma; Onset/offset fullfield ERG; Photopic negative response